Switching of Band Selection for Micro Scale RF Energy Harvesting - De Silva , D. S.; Pirapaharan, K.; Gunawickrama, S. H. K. K.; De Silva, M. S. S. R.; T. L. K. C. Dharmawardhana; W. G. D. C. Indunil; C. B. Wickramasinghe; C. V Aravind; John Wiselin (Asian Journal of Electrical Sciences, 2013)
Radio-frequency energy harvesting keeps a significant space for gathering a small amount of electrical power to drive specific circuits in wireless electronic devices.This paper presents the concept for band selection in order to provide a fair spectrum management process for micro scale energy harvesting in the radio frequency spectrum. The performance based on the associated power of the frequency channels at ambient and busy conditions is investigated in this work.